2020
DOI: 10.1097/iop.0000000000001424
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Nonvisual Afferent Sensory Upper Eyelid Proprioception

Abstract: The authors describe proprioception in the upper eyelid: A histologic analysis. Purpose: Recent research has suggested a possible role for proprioception in ipsilateral frontalis activation in the setting of ptosis; however, there has not been any robust histologic or anatomic evidence to support this theory. To further elucidate proprioceptive structures in the eyelid, this investigation uses validated histologic techniques to explore the presence of proprioceptive structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
8
4
Order By: Relevance
“…1 In comparison, another study done in the US did not find any muscle spindles at all in the LPS muscles of human adults aged 47 to 77 years. 8 The difference between this study and ours may be due to racial and methodological disparities. 8 All muscle spindles were found in the most proximal section (the muscle origin) of the LPS muscle in this study.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…1 In comparison, another study done in the US did not find any muscle spindles at all in the LPS muscles of human adults aged 47 to 77 years. 8 The difference between this study and ours may be due to racial and methodological disparities. 8 All muscle spindles were found in the most proximal section (the muscle origin) of the LPS muscle in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…3,4 In contrast, muscle spindles in the levator palpebrae superioris (LPS) muscle have little been elucidated in human adults. 4,5,8 A previous report examined muscle spindles in the LPS muscle but this study was conducted in human foetuses. 1 Studies that examined muscle spindles in the LPS muscle in human adults either found no muscle spindles in the LPS 8 or did not discuss their findings at all.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…80 Ipsilateral frontalis muscle activation in anophthalmic patients with ptosis is an interesting phenomenon that demonstrates the presence of non-visual stimuli in frontalis recruitment, showing that a sensory trigger -and not a visual stimulus -might be responsible for frontalis recruitment in these patients. 81,82 Histologic studies have confirmed the presence of Golgi tendon organs, muscle spindles, and myotendinous cylinders within the levator muscle, 83 and neural structures have been demonstrated in Müller's muscle fibers. 84 These nerve terminals may be implicated in proprioception, and the pathway for frontalis contraction might originate in proprioceptive fibers in the Müller's muscle through the trigeminal ganglion.…”
Section: Ptosis In Anophthalmic Patientsmentioning
confidence: 94%
“…82 The eyelid, in close contact with the prosthesis, may provide an alternative pathway to stimulate ipsilateral frontalis recruitment. [83][84][85]…”
Section: Ptosis In Anophthalmic Patientsmentioning
confidence: 99%